Scorpion venom polypeptide governs alveolar macrophage M1/M2 polarization to alleviate pulmonary fibrosis. (December 2022) - Xu, Liping; Zhang, Yan; Dai, Qiaoding; Lin, Na; Guan, Tianrong; Song, Xinwei; Hong, Shouhai
Abstract: The onset of connective tissue disease-related interstitial lung disease (CTD-ILD) is generally insidious and progressive, with pulmonary fibrosis in the middle stage, and eventually respiratory failure and death. This study aimed to explore the role of scorpion venom polypeptide (SVP), the primary active constituent of the entire scorpion, in alveolar macrophages and pulmonary fibrosis. Pulmonary fibrosis mouse models were established, and then SVP and JAK inhibitor (tofacitinib) was used to treat models. Alveolar macrophages were isolated and the impacts of SVP on M1/M2 polarization and the JAK/STAT6 pathway in vitro were assessed. H&E and Masson staining revealed that SVP and tofacitinib treatment alleviated lung damage and fibrosis. They also hindered the M2-polarization of macrophages in lung tissue and declined cytokine levels associated with M2 polarization (IL-4, IL-13) and fibrosis drivers (TGF-β, VEGF) in mice. Consistent with the trend presented by tofacitinib treatment, SVP suppressed the phosphorylation of proteins in the JAK/STAT6 pathway. In addition, the in vitro treatment of SVP on the isolated macrophages represented consistent results with in vivo experiments. The findings of the present study indicated that SVP suppressed the JAK/STAT6 signaling pathway, hindered alveolar macrophage M2-type polarization, and possessed the potential to ameliorate pulmonary fibrosis. Graphical Abstract: ga1 Highlights: Scorpion venom polypeptide alleviates pulmonary fibrosis. Scorpion venom polypeptide governs macrophage M1/M2 polarization. Scorpion venom polypeptide suppresses the JAK/STAT signaling.